DNA microarray technology in medical diagnostics - Damjana Rozman (Zdravniški Vestnik, 2007)
Background: DNA microarray technology opened a completely new venue in the biomedical research. By allowing to follow the expression of thousands of genes in a single experiment (ideally we can follow the expression of the entire genome), the microarray technology brings new perspectives for improvement of prognostics and diagnostics of complex human diseases. By SNP arrays that allow identification of individual patient’s genotype for frequent genetic diseases, this technology contributes to the efforts towards personalized medicine. Methods: Different approaches to microarray technology are presented with some examples of its application in medicine and pharmacogenomics. Practical considerations for using microarrays are described, including selecting an appropriate platform, designing and performing an experiment, and managing data. Statistical issues in microarray data analysis are raised and the most common analysis techniques are listed. In conclusion the current state of microarray technology in Slovenia is addressed.